(untitled) (Journal of Universal Excellence, 2026)
Research Question: In supplier-customer relations, negotiations are pivotal for shaping collaboration and outcomes. This study has a dual focus: first, it explores modern techniques that favour creative reciprocity over traditional price talks; second, it details alternative approaches for reaching mutually beneficial agreements. The overarching questions guiding this study are: "What are the principles for obtaining alternative proposals to commercial approaches to negotiation?" and "What are concrete alternative proposals to the commercial negotiation approach?" The goal is to transition from conventional to more integrative negotiation methods that benefit both parties. Purpose: The research aims to raise awareness of supplier-customer collaboration and the importance of mutual goals, particularly in joint development and tech-sharing contexts. It introduces a modern approach to commercial agreements that shifts focus from short-term price talks to long-term mutual benefits. Method: The first part of the research defines the analytical tool for text interpretation, backed by literature review. The second part presents findings from semi-structured interviews and observations, analysed via thematic network analysis. This approach provides a thorough understanding of supplier-customer negotiation dynamics. Results: The results of the qualitative research are presented using thematic network analysis, with in-depth analysis and explanation. Findings are summarized descriptively, offering principles for negotiators and specific alternative proposals to traditional negotiation methods. This approach provides nuanced insights for commercial negotiations. Organization: The study raises awareness of the drawbacks of traditional price negotiations while providing guidelines for modern commercial deals. Negotiators can use these modern alternatives to achieve their goals, reducing organizational constraints and enhancing reputation. Society: The entire society can benefit from mutual organizational understanding, resolving negotiation conflicts, and reaching agreements. This not only enhances individual organizational reputations but also contributes to overall social cohesion and economic stability. Originality: The research suggests replacing traditional price negotiations with modern commercial agreements in the supplier-customer relationship, into more collaborative interactions. Limitations / further research: The research is limited to the sources cited in the literature and interviews with four different profiles. The study is based on the mutual cooperation of the buyer and the supplier in a long-term partnership, thereby excluding the behaviours of the traditional commercial negotiation approach.